Assessing the implications of EU Nature Restoration Law targets from carbon sequestration and biodiversity perspectives in a high-green urban environment - Antti Kinnunen; Ranja Hautamäki; Jaana B. Junnila; Joel Jalkanen; Leena Järvi; Liisa Kulmala; Jussi Lampinen; Minttu Havu; Seppo Junnila; Christopher Raymond (npj Urban Sustainability)
Abstract In response to the urgent environmental crises, the European Union has intensified legislative actions, including the Nature Restoration Law (NRL). The NRL provides a framework aimed at halting and reversing the degradation of ecosystems and biodiversity loss across the EU. A pivotal element of the NRL is Article 8, dedicated to the restoration of urban ecosystems. While the outlined land use measures limit environmental degradation, they also raise concerns about how cities will manage these requirements with a simultaneously growing population. We examine the potential implications of the NRL on carbon sequestration and biodiversity in Helsinki, Finland, assessing the impacts under various urban development scenarios. Our results indicate that whilst the law presents an improvement compared to business-as-usual growth, this is contrasted with increasing density as cities need to accommodate the growing population. The research, therefore, advocates for an approach merging top-down quantitative targets with qualitative, locally tailored actions.